2002
DOI: 10.1104/pp.002337
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Acts as an Antioxidant and Delays Programmed Cell Death in Barley Aleurone Layers

Abstract: Nitric oxide (NO) is a freely diffusible, gaseous free radical and an important signaling molecule in animals. In plants, NO influences aspects of growth and development, and can affect plant responses to stress. In some cases, the effects of NO are the result of its interaction with reactive oxygen species (ROS). These interactions can be cytotoxic or protective. Because gibberellin (GA)-induced programmed cell death (PCD) in barley (Hordeum vulgare cv Himalaya) aleurone layers is mediated by ROS, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(201 citation statements)
references
References 32 publications
8
192
0
1
Order By: Relevance
“…Likewise, a similar mechanism may be operating in par2-1, and the NO donor SNP confers paraquat resistance, presumably by exerting an antagonistic effect against the oxidative stress through increasing the NO level. This view is supported by the observation that SNP also confers paraquat resistance to potato leaves [52], and acts as an antioxidant to delay PCD induced by gibberellin in barley aleurone layers [33]. Again, consistent with the reciprocal regulation of NO and ROS, the accumulation of GSNOR1/HOT5/PAR2 protein is induced by paraquat, but is reduced when treated by SNP and GSNO.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Likewise, a similar mechanism may be operating in par2-1, and the NO donor SNP confers paraquat resistance, presumably by exerting an antagonistic effect against the oxidative stress through increasing the NO level. This view is supported by the observation that SNP also confers paraquat resistance to potato leaves [52], and acts as an antioxidant to delay PCD induced by gibberellin in barley aleurone layers [33]. Again, consistent with the reciprocal regulation of NO and ROS, the accumulation of GSNOR1/HOT5/PAR2 protein is induced by paraquat, but is reduced when treated by SNP and GSNO.…”
Section: Discussionsupporting
confidence: 70%
“…Because NO has been reported to act as an antioxidant [28,32,33], we reasoned that the paraquat-resistance phenotype of par2-1 may be related to the increased intracellular NO level in the mutant. To test this possibility, wild type, par2-1 and gsnor1-3 were germinated and grown in the presence of NO donors, sodium nitroprusside (SNP) and GSNO, or the NO scavenger, 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidadazoline-1-oxy-3-oxide (CPTIO).…”
Section: Paraquat Resistance Is Enhanced By No Donor Snpmentioning
confidence: 99%
See 1 more Smart Citation
“…Tu et al (2003) reported that wheat leaves treated with 0.10 m mol/L SNP reduced H 2 O 2 by activating catalase in ageing wheat leaves. Beligni et al (2002) found that SNAP (Snitroso-N-acetyl-DL-pericillamine), another NO donor, could delay the GA-induced loss of Cat2 mRNA and protein in barley aleurone. also reported that SNP increased the activity of peroxidase but had little effect on SOD in drought stressed poplar leaves.…”
Section: Discussionmentioning
confidence: 99%
“…S3C). Butylated hydroxytoluene (BHT) and ascorbate acid (AsA) are efficient antioxidants (Beligni et al, 2002), and diphenylene iodonium (DPI) is an inhibitor of the plasma membrane NADPH oxidase that is one of the main sources of H 2 O 2 generation after an environmental stress (Neill et al, 2002;Torres and Dangl, 2005). BHT, AsA, and DPI suppressed 3-O-C10-HL-induced H 2 O 2 accumulation ( Three-day-old mung bean explants were subjected to 100 nM 3-O-C10-HL or a donor (100 nM C10-HL, 10 mM IAA, 100 mM H 2 O 2 , 50 mM GSNO, or 1 mM 8-Br-cGMP) treatment for 3 d or were pretreated with different inhibitors or scavengers (10 mM NPA, 1 mM DPI, 1 mM BHT, 1 mM AsA, 50 mM cPTIO, 10 mM LY83583, or 50 mM ODQ) for 2 h. This treatment was followed by the addition of 100 nM 3-O-C10-HL for 24 h, and H 2 O 2 (A) and NO (B) contents were determined.…”
Section: -O-c10-hl Induces Adventitious Root Formation In Mung Bean mentioning
confidence: 99%